Comparative analysis of zooplankton diversities and compositions estimated from complement DNA and genomic DNA amplicons, metatranscriptomics, and morphological identifications. (18th June 2021) - Machida, Ryuji J; Kurihara, Haruko; Nakajima, Ryota; Sakamaki, Takashi; Lin, Ya-Ying; Furusawa, Kazushi
Abstract: Community-based diversity analyses, such as metabarcoding, are increasingly popular in the field of metazoan zooplankton community ecology. However, some of the methodological uncertainties remain, such as the potential inflation of diversity estimates resulting from contamination by pseudogene sequences. Furthermore, primer affinity to specific taxonomic groups might skew community composition and structure during PCR. In this study, we estimated OTU (operational taxonomic unit) richness, Shannon's H', and the phylum-level community composition of samples from a coastal zooplankton community using four approaches: complement DNA (cDNA) and genomic DNA (gDNA) mitochondrial COI (Cytochrome oxidase subunit I) gene amplicon, metatranscriptome sequencing, and morphological identification. Results of mismatch distribution demonstrated that 90% is good threshold percentage to differentiate intra- and inter-species. Moderate level of correlations appeared upon comparing the species/OTU richness estimated from the different methods. Results strongly indicated that diversity inflation occurred in the samples amplified from gDNA because of mitochondrial pseudogene contamination (overall, gDNA produced two times more richness compared with cDNA amplicons). The unique community compositions observed in the PCR-based methods indicated that taxonomic amplification bias had occurred during the PCR. Therefore, it is recommended that PCR-free approaches be used whenever resolving community structure represents an essential aspect of the analysis.